Tracking crop varieties using genotyping-by-sequencing markers: a case study using cassava (Manihot esculenta Crantz) - Rabbi, Ismail Y.; Kulakow, Peter A.; Manu-Aduening, J.A.; Dankyi, Ansong A.; Asibuo, James Y.; Parkes, Elizabeth Y.; Abdoulaye, Tahirou; Girma, Gezahegn; Gedil, Melaku A; Ramu, Punna; Reyes, Byron A.; Maredia, Mywish K. (Springer, 2015)
Accurate identification of crop cultivars is crucial in assessing the impact of crop improvement research outputs. Two commonly used identification approaches, elicitation of variety names from farmer interviews and morphological plant descriptors, have inherent uncertainty levels. Genotyping-by-sequencing (GBS) was used in a case study as an alternative method to track released varieties in farmers’ fields, using cassava, a clonally propagated root crop widely grown in the tropics, and often disseminated through extension services and informal seed systems. A total of 917 accessions collected from 495 farming households across Ghana were genotyped at 56,489 SNP loci along with a “reference library” of 64 accessions of released varieties and popular landraces.